Географія ринку цінних паперів(облігацій) на Буковині в австрійські часи: періоди формування та розгортання (1790/1870-1914/18) - Огуй, О. (Інститут історії України НАН України, 2007)
Автор даної статті досліджує періодизацію та вивчає географічні особливості обігу цінних паперів на Буковині протягом XVIII–XX ст. Розвідка написана на основі детального вивчення великого фактичного матеріалу з приватних колекцій. Докладно розглянуто питання періодів формування ринку цінних паперів на цій території. This paper deals with the economic history of Bukovina, former part of dukedom Moldova (with no developed system of value papers). Bukovina was involved to this system fi rstly by inner Austrian means: bancozettles, later on by war loans, state loans, indomnesiation obligations etc., then by different means: Austrian-Hungarian and foreign obligations. The geography of foreign obligations (described upon the basis of 3 Bukovinian collections: about 80 obligations) demonstrates on one hand the dominance to the inner monarchy market, and on the second hand the tendency to the Balkans (Turkey, Serbia) and to Holland and Swiss.